2004
DOI: 10.1152/ajprenal.00139.2003
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II induces thrombospondin-1 production in human mesangial cells via p38 MAPK and JNK: a mechanism for activation of latent TGF-β1

Abstract: ANG II induces secretion and activation of transforming growth factor-beta (TGF-beta) by glomerular mesangial cells. However, the mechanisms that operate this are unclear. Thrombospondin-1 (TSP-1), which is produced by mesangial cells in damaged glomeruli, is one of several molecules known to activate the latent TGF-beta1 complex. Therefore, we examined whether the ANG II-induced activation of latent TGF-beta1 in human mesangial cells (HMC) operates via TSP-1. The addition of ANG II (1-100 nM) to HMC significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
93
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(105 citation statements)
references
References 41 publications
10
93
0
1
Order By: Relevance
“…These data suggest that a pathway or pathways other than PI3K-AKT regulate TSP-1 expression. Delayed activation of p38 mitogen-activated protein kinases (MAPK) has been reported to regulate TSP-1 expression in other cancer cell types (Takekawa et al, 2002;Naito et al, 2004). Early activation of p38 kinase by the anti-HER2 antibody ID5 was reported previously (Le et al, 2000).…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…These data suggest that a pathway or pathways other than PI3K-AKT regulate TSP-1 expression. Delayed activation of p38 mitogen-activated protein kinases (MAPK) has been reported to regulate TSP-1 expression in other cancer cell types (Takekawa et al, 2002;Naito et al, 2004). Early activation of p38 kinase by the anti-HER2 antibody ID5 was reported previously (Le et al, 2000).…”
Section: Resultsmentioning
confidence: 80%
“…In other cell systems, delayed activation of the p38 MAP kinase pathway also has a negative impact on cell proliferation by inducing apoptosis (Daly et al, 1999;Takekawa et al, 2002;Bulavin and Fornace, 2004;Naito et al, 2004). Treatment of BT474 and SKBr3 cells with anti-HER2 antibodies for 72 h does not induce significant apoptosis (Le et al, 2003(Le et al, , 2005a.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MAPKs are pivotal mediators of the effects of Ang II on tissue structure by increasing TGF‐β1 expression, leading to atrial fibrosis 38, 39, 40. TGF‐β1 is a cytokine that regulates cell proliferation, apoptosis, migration, and synthesis of ECM, such as fibronectin and collagen in the atrium 41, 42.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have shown that antagonism of angiotensin II signaling results in decreased TGF-b signaling in a variety of tissues, including kidney, lung, skeletal muscle, heart, and aorta (Shihab et al 1997;Sun et al 1998;Lavoie et al 2005;Habashi et al 2006;Yao et al 2006;Cohn et al 2007;Podowski et al 2012), the exact mechanism by which this occurs is not fully understood (Gibbons et al 1992;Stouffer and Owens 1992;Wolf et al 1993Wolf et al , 1999Kagami et al 1994;Lee et al 1995;Campbell and Katwa 1997;Fukuda et al 2000;Boffa et al 2003;Naito et al 2004;RodriguezVita et al 2005;Zhou et al 2006;Chen et al 2013). Suppression of excessive Erk1 and Erk2 MAPK activation with losartan or an inhibitor of MAPK kinase (MAPKK, also known as MEK) has been shown to normalize aortic architecture and aneurysm pathology in MFS mouse models (Habashi et al 2011), indicating that Erk MAPK activation is critical to aneurysm progression.…”
Section: Tgf-b Family Signaling In Connective Tissuesmentioning
confidence: 99%